Designing preschool interventions : a practitioner's guide - Barnett, David W.; Bell, Susan H.; Carey, Karen T. (New York : Guilford, 1999)
Critical issues in preschool interventions
Consulting with parents and teachers
Principles and techniques for observing
Designing effective interventions
Evaluating intervention design and outcomes
Developing new behaviors and modifying existing behaviors
Managing severe problem behaviors
Changing roles within family systems
Parent interventions for severe and risk-related problem behaviors
The classroom as ecosystem
Classroom social and safety-related interventions
Bibliografija
Kazala
Keywords: djeca predškolške dobi; problemi u ponašanju; poteškoće u učenju